A CONCEPTUAL PAPER ON SHARIAH-COMPLIANT BUY NOW PAY LATER (BNPL): REVIEWING LITERATURE AND IDENTIFYING RESEARCH GAPS - Norsyuhada Ismail; Anizah Zainuddin; Amily Fikry (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The advent of Buy Now Pay Later (BNPL) services has precipitated a paradigm shift in consumer financing, ushering in a new era of flexible payment options within the digital commerce landscape. While substantial research has been conducted on conventional BNPL models, there has been limited exploration of Shariah-compliant alternatives that are in alignment with Islamic financial principles. As demand for ethical, interest-free financing increases, Shariah-compliant BNPL emerges as a viable alternative to conventional credit-based systems. However, a comprehensive examination of the influence of religious values on consumer behaviour, particularly within the context of Islamic finance, remains a significant gap in the current literature. This paper critically reviews existing research on BNPL adoption and ethical financial practices, identifying notable gaps, especially regarding consumer awareness of Shariah-compliant options and their decision-making processes. By synthesizing the findings of previous studies, this paper identifies significant theoretical limitations and puts forward recommendations for future research directions. A more profound comprehension of the factors influencing the adoption of Shariah-compliant BNPL is imperative for enhancing financial literacy, fostering consumer trust, and promoting sustainable ethical finance. This study makes a significant contribution to the expanding domain of Islamic fintech by offering actionable insights for policymakers, financial institutions, and researchers who aim to develop and promote inclusive, Shariah-compliant financial solutions.